Fucoxanthin prevents cell growth and induces apoptosis in endometrial cancer HEC‐1A cells by the inhibition of the PI3K/Akt/mTOR pathway. Issue 6 (9th March 2022) - Qu, Jinfeng; Sun, Yaping; Yang, Lukai; Niu, Xiaoxiao; Li, Lanyu
Abstract: Endometrial cancer is the major type of gynecological cancer and ranks as the sixth most common cancer in women. Endometrial cancer usually is diagnosed in an advanced stage, complicating the treatments in many cases. The present research was focused on unveiling the in vitro anticancer role of fucoxanthin against the endometrial cancer HEC‐1A cells by inhibiting the phosphatidylinositol‐3‐kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling axis. The cytotoxicity of fucoxanthin against the endometrial cancer HEC‐1A cells was studied using the MTT test. The level of reactive oxygen species (ROS) production, mitochondrial membrane potential (MMP) status, and apoptotic cell death in the 7.5 and 10 µM administered HEC‐1A cells were assayed using fluorescent staining techniques. The messenger RNA expression was analyzed using RT‐PCR for PI3K/Akt/mTOR signaling molecules, proapoptotic (Bax and caspase‐3) antiapoptotic (cyclin D1 and Bcl‐2) genes, and inflammatory markers like tumour necrosis factor α (TNFα), nuclear factor kappa B (NF‐κB), Cox‐2, and interleukin (IL)‐6. The cell viability assay proved that fucoxanthin effectively prevented HEC‐1A cell viability, where the IC50 was 7.5 µM. Fucoxanthin at 7.5 and 10 µM remarkably improved ROS production and apoptosis and decreased the MMP in HEC‐1A cells. The fucoxanthin effectively inhibited the PI3K/Akt/mTOR cascade along with the expression of TNF‐α, NF‐κB, Cox‐2, and IL‐6 and antiapoptotic genes cyclin D1 and Bcl‐2 in the HEC‐1A cells. Fucoxanthin treatment also enhanced the Bax and caspase‐3 expressions in the HEC‐1A cells. Our results from this work unveiled that fucoxanthin triggered growth inhibition and apoptosis in endometrial cancer HEC‐1A cells. Besides, fucoxanthin inhibited the PI3K/Akt/mTOR cascade and improved apoptotic marker expressions in the HEC‐1A cells.